The effect of fish density and tank size on the behavior of adult zebrafish: A systematic analysis - Shishis, Stephanie; Tsang, Benjamin; Gerlai, Robert (Frontiers in Behavioral Neuroscience, 2022)
The zebrafish has been employed in several fields of biology due to its translational relevance and its simplicity and ease of maintenance. As a result, zebrafish are kept in thousands of laboratories around the world. Current industry standards favour keeping the largest possible number of fish in the smallest possible volume of water to increase efficiency and reduce costs. However, physiological and psychological stress resulting from such crowding may impact a variety of phenotypes, from brain function and behaviour to cardiovascular function and cancer. Nevertheless, surprisingly little is known about what constitutes an optimal housing environment for the zebrafish, e.g., no systematic analyses have been performed to test the role of housing density and tank volume despite recent sporadic reports implying negative effects of the standard practice of crowding. Here, we conduct the first proof of concept analysis examining the potential impact of housing density and tank volume on the behaviour of zebrafish. We randomly assigned adult zebrafish to one of three tank sizes (1.5L, 10L or 50L) with one of three housing densities (1, 2 or 4 fish/L), a 3x3 between subject experimental design, and maintained the fish in their corresponding condition for 2 weeks. Subsequently, we tested the behavior of the fish singly in a novel open tank for 12 min and quantified several of their swim path parameters using a video-tracking system. We found significant additive and interacting effects of tank size and/or housing density on swim path parameters including immobility, swim speed, turn angle, and distance to bottom and to stimulus. Although we had only 3 fish densities and 3 tank sizes and we did not explore the effects of more extreme conditions and although the interpretation of the above behavioural effects is speculative at this point, the results already demonstrate that both tank size and housing density exerts significant effects on the zebrafish and thus should be considered in zebrafish husbandry.